Learning Programming using Lego Mindstorm : Analysis of Learner Experiences - Tengku Mohd Noor, Tengku Farah Hanum Nor; Fitri Suraya, Mohamad; Jacey Lynn, Minoi (IEEE, 2020)
We conducted an experiment to investigate the viability of using Lego Mindstorms as an alternative approach to supplement the learning of Basic Programming among novice university students. The study captured reactions and responses from ten undergraduates who had no background in Programming and were facing difficulties coping with an introductory course in Programming. Four Lego Mindstorm units were deployed to examine the participants’ problem-solving and computational thinking skills. Findings indicate a high positive response to the use of Mindstorms as a strategy to encourage higher-order thinking, a key skill in learning Programming. Participants reported clarity in understanding computational thinking concepts and claimed to be better able to articulate problem-solving tasks when prompted using Mindstorm.